2020
DOI: 10.1051/0004-6361/202037493
|View full text |Cite
|
Sign up to set email alerts
|

Event Horizon Telescope imaging of the archetypal blazar 3C 279 at an extreme 20 microarcsecond resolution

Abstract: 3C 279 is an archetypal blazar with a prominent radio jet that show broadband flux density variability across the entire electromagnetic spectrum. We use an ultra-high angular resolution technique – global Very Long Baseline Interferometry (VLBI) at 1.3 mm (230 GHz) – to resolve the innermost jet of 3C 279 in order to study its fine-scale morphology close to the jet base where highly variable γ-ray emission is thought to originate, according to various models. The source was observed during four days in April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 101 publications
2
41
0
Order By: Relevance
“…The jet-like feature is oriented at approximately 40°, i.e., is roughly aligned with the EVPA in the core. Ultra-high-resolution images with the EHT reveal a jet component approximately along the same PA but on angular scales 10 5 times smaller (Kim et al 2020).…”
Section: Agnsmentioning
confidence: 91%
“…The jet-like feature is oriented at approximately 40°, i.e., is roughly aligned with the EVPA in the core. Ultra-high-resolution images with the EHT reveal a jet component approximately along the same PA but on angular scales 10 5 times smaller (Kim et al 2020).…”
Section: Agnsmentioning
confidence: 91%
“…The recovery of D-terms for a highly polarized source like 3C 279 would require an extremely accurate source model in both total intensity and polarization. However, 3C 279ʼs complex structure in both total and polarized intensity add to the difficulty of imaging and calibrating the source (Kim et al 2020). Furthermore, interferometric-ALMA measurements taken contemporaneously to our EHT campaign found that 3C 279 may have non-negligible Stokes  (see Goddi et al 2021), which breaks the Stokes =  0 assumptions made in most of our calibration and imaging pipelines.…”
Section: I2 Image-averaged Quantitiesmentioning
confidence: 99%
“…For full-array leakage calibration, we focus on two additional sources: J1924-2914 and NRAO 530 (calibrators for the second EHT primary target, Sgr A * ), which are compact and relatively weakly polarized. The main calibrator for M87 in total intensity, 3C 279 (Kim et al 2020;Paper IV), is bright and strongly polarized on longer baselines and is not used in this work. The properties and analysis of the calibrators are discussed in more detail in Appendices J and K.…”
Section: Polarimetric Data Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…With results from the 2017 EHT campaign for 3C 279 already published (Kim et al 2020) 2021, in preparation), and many more in the pipeline, we expect the context and impact of the multi-wavelength results to significantly broaden in the coming years. The precision EHT mm-VLBI images together with broadband SED information will be essential ingredients for developing a fuller understanding of the AGN phenomenon.…”
Section: Discussionmentioning
confidence: 99%